Double detonations: variations in Type Ia supernovae due to different core and He shell masses; II. Synthetic observables - Collins, Christine E.; Gronow, Sabrina; Sim, Stuart A; Röpke, Friedrich (Monthly notices of the Royal Astronomical Society, 2022)
Double detonations of sub-Chandrasekhar mass white dwarfs are a promising explosion scenario for Type Ia supernovae, whereby a detonation in a surface helium shell triggers a secondary detonation in a carbon-oxygen core. Recent work has shown that low-mass helium shell models reproduce observations of normal SNe Ia. We present 3D radiative transfer simulations for a suite of 3D simulations of the double detonation explosion scenario for a range of shell and core masses. We find light curves broadly able to reproduce the faint end of the width-luminosity relation shown by SNe Ia, however, we find that all of our models show extremely red colours, not observed in normal SNe Ia. This includes our lowest mass helium shell model. We find clear Ti ii absorption features in the model spectra, which would lead to classification as peculiar SNe Ia, as well as line blanketing in some lines of sight by singly ionized Cr and Fe-peak elements. Our radiative transfer simulations show that these explosion models remain promising to explain peculiar SNe Ia. Future full non-LTE simulations may improve the agreement of these explosion models with observations of normal SNe Ia.
Gesehen am 20.01.2023